Waste graphite-based rate type artificial graphite negative electrode material as well as preparation and application thereof
Through resonance mixing, ultrasonic-assisted thermal isostatic pressure and gradient insulation treatment, the problems of high energy consumption and structural damage in the recycling process of waste graphite are solved, and graphite materials with high rate performance are prepared, which are suitable for the negative electrode of lithium-ion batteries.
Patent Information
- Application Number
- CN202510285295.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-07-04
AI Technical Summary
The existing graphite preparation process has high energy consumption, high cost and is difficult to regenerate waste graphite materials into negative electrode materials with high rate performance. Waste graphite affects ion and electron conduction due to structural damage and impurities.
The waste graphite powder is resonantly mixed with additive A to form primary particles, and then heat isostatic pressure treatment with the binder and coke raw material assisted by ultrasonic. After two stages of gradient insulation treatment, carbon coating is finally carried out to form graphite material with high magnification performance.
It realizes efficient preparation of high-rate performance graphite materials in a short process, solves structural damage and impurities problems in the recycling process of waste graphite, and optimizes the circulation performance of the material.
Smart Images

Figure CN120247011A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of battery materials, and particularly relates to the field of graphite anode materials for batteries. Background Art
[0002] In today's society where green energy is developing rapidly, new energy vehicles have achieved rapid development. As a key component of new energy vehicles, the energy density of lithium-ion batteries has also increased rapidly with technological progress, enabling pure electric vehicles to generally travel more than 500 km, meeting the basic daily usage needs of people. In addition, the "fast charging anxiety" of electric vehicles and the "high power" operating conditions of energy storage have put forward higher requirements for the charging speed of LIBs systems. Fast charging means charging 80% of the battery capacity within 15 minutes, that is, the battery can stably operate under a high rate condition of at least 4C (1C represents the current intensity when the battery is fully discharged in one hour). Therefore, on the premise of maintaining the safety, environmental protection, low cost, and long cycle life of LIBs, improving their fast charging performance and power characteristics is of great significance for promoting the development of industries such as electric vehicles, consumer electronic devices, and energy storage technologies.
[0003] Graphite is the most commonly used anode material for LIBs, with advantages such as high energy density, low voltage, good electrical conductivity, rich resources, and low price. It will still be the primary choice for LIBs anode materials for a long time to come. However, the conventional preparation processes of existing rate-type anode materials include powder making, granulation, pre-carbonization, high-temperature graphitization, carbon coating, etc. The main problems faced in this preparation process are: 1. The process flow is long and complex, resulting in low efficiency and high costs. After the raw materials are made into powder, they need to go through the granulation process, which has low production capacity and high costs. 2. When using petroleum coke or needle coke as raw materials, they need to go through the high-temperature graphitization process and can only be used as anode materials after reaching a certain degree of graphitization. The existing mass-production high-temperature graphitization processes usually use Acheson furnaces or box furnaces, which require a large amount of auxiliary materials and consumables such as crucibles, thermal insulation materials, and resistance materials, and are batch production. The production cycle is 25 - 45 days, and most of the time is for cooling. The loss of this part of energy is not effectively utilized, resulting in extremely high energy consumption during the graphitization process.
[0004] To solve the problems of high energy consumption and high cost in the existing graphite preparation, it is expected to reduce the graphitization cost by using waste graphite with a relatively high degree of graphitization from waste battery materials. However, due to long-term cycling, there are significant structural damages and impurities in the interlayer of waste graphite materials. If the problems faced by waste graphite cannot be properly solved, it is difficult to recycle it for the regeneration preparation of rate-type graphite materials and difficult to obtain the expected high-rate stability. Summary of the Invention
[0005] In view of the problem that waste graphite materials are difficult to recycle to obtain materials with excellent rate performance, the first purpose of the present invention is to provide a method for preparing waste graphite-based rate-type artificial graphite negative electrode materials, aiming to utilize waste graphite to efficiently prepare graphite active materials with high rate and electrochemical properties.
[0006] The second purpose of the present invention is to provide a waste graphite-based rate-type artificial graphite negative electrode material prepared by the preparation method and its application as a negative electrode active material in preparing lithium-ion batteries.
[0007] The third object of the present invention is to provide a lithium ion battery comprising the waste graphite-based rate-type artificial graphite negative electrode material, and its negative electrode and negative electrode material.
[0008] Although waste graphite has a good degree of graphitization, it has many defects and structural damage on the surface and between layers due to long-term circulation, and also contains a large number of harmful impurities. Using it will easily affect the conduction network of ions and electrons, making it difficult to regenerate high-rate materials. In view of this problem, the present invention has provided the following improvement plan after in-depth research:
[0009] A method for preparing a waste graphite-based rate-type artificial graphite negative electrode material, comprising resonantly mixing waste graphite powder and an additive A to obtain primary particles; wherein the additive A comprises at least one of boric acid, boron carbide, boron nitride, boron oxide, iron carbide, metal M and its compound; the metal M comprises at least one of iron, cobalt, nickel, chromium, molybdenum, manganese and magnesium; the compound of the metal M comprises one or more of the oxide, sulfide, halide, metal salt and metal organic complex of the metal M;
[0010] The primary particles, the binder and the coke raw material are subjected to hot isostatic pressing under the assistance of ultrasound to obtain secondary particles; wherein the weight ratio of the waste graphite powder and the coke raw material in the primary particles is 1-4:6-9;
[0011] The secondary particles are preliminarily subjected to a first stage of heat preservation treatment at a temperature of 800 to 1200° C. in an atmosphere A containing a protective gas, and then subjected to a second stage of heat preservation treatment at a temperature of 2000 to 2800° C. in an atmosphere B containing an additive B, to obtain a graphite material; the additive B is at least one of FeCl3, NiCl, and CoCl2;
[0012] The graphite material is post-processed to obtain the waste graphite-based rate-type artificial graphite negative electrode material.
[0013] In the present invention, waste graphite is innovatively subjected to resonance mixing treatment with additive A in advance, and then ultrasonic-assisted hot isostatic pressing treatment is carried out with a binder and a coke raw material in a special ratio. Further, in combination with subsequent two-stage heat preservation and the combined control of the atmosphere during the heat preservation stage, synergism can be unexpectedly achieved, and the damaged interlayers of waste graphite can be synergistically repaired from the inside to the outside, reducing interlayer impurities and optimizing its cycle performance. In addition, based on the combination from the inside to the outside, complete graphitization of the regenerated material from the inside to the outside can be constructed. The method described in the present invention can regenerate a graphite material with high rate performance based on waste graphite.
[0014] In the present invention, the waste graphite powder is a graphite-containing waste material disassembled and peeled from waste batteries;
[0015] Preferably, in the waste graphite powder, the content of graphite is above 90 wt.%.
[0016] Preferably, the D50 of the waste graphite powder is 8 - 20 um, and the ash content is < 10 wt.%.
[0017] The additive A is at least one of nano Fe3C, nano Fe2O3, FeCl3, NiCl, and CoCl2. The additive A can be used in solid form or in solution form.
[0018] Preferably, the additive A includes Fe3C and FeCl3; further, the weight ratio of the two can be 0.5 - 2:1. Research shows that the preferred additive A can cooperate synergistically with the process of the present invention, which helps to further optimize the high fast charging performance of the prepared material.
[0019] Preferably, the weight ratio of waste graphite powder to additive A is 1:0.001 - 0.05, and further can be 1:0.005 - 0.02.
[0020] Preferably, the particle size of the primary particles is 8 - 15 um.
[0021] Preferably, the frequency of resonance mixing is 30 - 100 Hz, and the time is 0.5 - 2 h.
[0022] In the present invention, the weight ratio of waste graphite powder to coke raw material in the primary particles is 2 - 4:6 - 8.
[0023] In the present invention, the binder includes at least one of vinyl tar, by-product tar, sodium carboxymethyl cellulose, resin, liquid-phase asphalt, water, and high molecular starch.
[0024] Preferably, the binder is 0.5 - 20% of the total weight of waste graphite powder and coke raw material, and more preferably 5 - 15%.
[0025] Preferably, the coke raw materials include at least one of petroleum coke and needle coke.
[0026] Preferably, the volatile matter of the coke raw materials > 6%, and D50 is 6 - 15 μm.
[0027] In the present invention, in the ultrasonic-assisted hot isostatic pressing stage, the power of the ultrasonic wave is 5 - 50 Hz; the temperature is 50 - 300 °C; the pressure is 10 - 200 MPa. Further, the power of the ultrasonic wave is 20 - 40 Hz; the temperature is 200 - 300 °C; the pressure is 50 - 150 MPa.
[0028] In the present invention, the ultrasonic-assisted hot isostatic pressing treatment step is, for example: pre-mix the primary particles, the binder and the coke raw materials, heat them to the temperature of hot isostatic pressing, then perform ultrasonic treatment, and subsequently perform pressure treatment.
[0029] In the present invention, before the ultrasonic-assisted hot isostatic pressing treatment, the mixture of the primary particles, the binder and the coke raw materials is pre-pressed. The pressure of the pre-pressing treatment can be 5 - 20 MPa. The pre-pressing time can be 20 - 50 min. Research shows that pre-pressing the mixture and then performing the subsequent ultrasonic-assisted hot isostatic pressing treatment can further improve the high-rate performance of the prepared material.
[0030] In the present invention, the protective gas in the atmosphere A of the first-stage heat treatment includes at least one of nitrogen and inert gas.
[0031] Preferably, the temperature of the first-stage heat treatment is 1000 - 1200 °C.
[0032] Preferably, the holding time of the first stage is 0.5 - 12 h, and further can be 1 - 3 h.
[0033] In the present invention, the additive B is in a gasified state at the said temperature, so that based on the three-phase characteristics of the treatment process, the physical and chemical structure of the material can be synergistically optimized, and thus the high-rate performance of the material can be synergistically improved.
[0034] Preferably, the additive B is FeCl3. Research shows that the preferred additive B can obtain better process synergy and can further optimize the high-rate performance of the material.
[0035] In the present invention, the atmosphere B of the second-stage heat treatment further contains a diluent gas. The diluent gas is argon, etc.
[0036] Preferably, in the atmosphere B, the dosage of the additive B is 0.05 - 10 v% of the weight of the waste graphite, and further can be 1 - 3%;
[0037] Preferably, the second insulation time is 2 to 8 hours, and further can be 4 to 6 hours; the method of the present invention can prepare materials with the required degree of graphitization in a shorter time, and the short-process and efficient preparation method can prepare high-rate materials.
[0038] Preferably, the post-treatment process includes a step of carbon coating the graphite material. The coating process can be conventional, for example, the second stage insulation material and the carbon source can be mixed and carbonized. The carbon source can be any organic matter that can form a single carbon substance, for example, it can be at least one organic matter in a solid, liquid, or gaseous state. The amount of the carbon source can be 1 to 15 wt% of the weight of the second stage insulation material. The carbonization temperature can be 400 to 1300°C.
[0039] The present invention also provides the waste graphite-based rate-type artificial graphite negative electrode material prepared by the preparation method.
[0040] In the present invention, thanks to the special preparation method, the prepared material can be endowed with special physical and chemical characteristics, and the material with the physical and chemical characteristics prepared by the preparation method can unexpectedly show excellent rate performance.
[0041] The present invention also provides an application of the waste graphite-based rate-type artificial graphite negative electrode material prepared by the preparation method, which is used as a negative electrode active material for preparing an alkali metal ion battery.
[0042] The present invention also provides an alkali metal ion battery, which comprises the waste graphite-based rate-type artificial graphite negative electrode material prepared by the preparation method.
[0043] The alkali metal ion battery of the present invention, in addition to comprising the waste graphite-based rate-type artificial graphite negative electrode material of the present invention, other components and structural parts can be known. The alkali metal ion battery can be, for example, a lithium ion battery.
[0044] Beneficial Effects
[0045] The present invention innovatively resonates and mixes waste graphite with additive A in advance to form primary particles, and then performs ultrasonic-assisted hot isostatic pressing with a binder and a special proportion of coke raw materials to form high-strength secondary particles, which are further coordinated with the subsequent combined control of gradient graphitization containing additive B. In this way, the problems faced by waste graphite regeneration can be solved based on internal and external synergy, and the physicochemical structure of the material can be optimized, thereby obtaining an artificial graphite negative electrode material based on waste graphite with good rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is a photo of the block obtained by pressing in step 3 of Example 1;
[0047] Figure 2 SEM image of the material obtained in Step 5 of Example 1. Detailed implementation manners
[0048] The waste graphite powder described in the present invention can be any graphite-containing waste that cannot be directly utilized. For example, as an alternative, the waste graphite powder selected in the following cases can be a graphite-containing waste material peeled from the negative electrode of a waste battery, wherein the final ash content is <0.5%, the volatile content is <3%, and the graphite content is 80 wt% - 95 wt%.
[0049] Example 1
[0050] 1) Mix waste graphite powder and additive A (nano Fe₃C) with a mass ratio of 100:0.8 in a VC mixer for 30 min until evenly mixed, and then place it in a resonance device for secondary mixing. The resonance frequency is 60 Hz and the time is 30 min. The waste graphite powder compounded with additive A is obtained after mixing.
[0051] 2) Pre-mix the waste graphite powder loaded with additive A, crushed petroleum coke, and vinyl tar evenly. The mass ratio of waste graphite powder to petroleum coke is 2:8, and the addition amount of vinyl tar is 15% of the total mass of waste graphite powder and petroleum coke. The D50 of petroleum coke is 11 μm and the volatile content is 6.5%.
[0052] 3) Place the material evenly mixed in Step 2 in a hot isostatic press. Four ultrasonic transducers are symmetrically arranged in the isostatic pressure cavity. First, pre-press the material at room temperature with 10 MPa; then heat up to 250 °C and turn on the ultrasound with a frequency of 20 Hz for ultrasonic-assisted isostatic pressing for 20 min; finally, increase the pressure to 150 MPa for high-pressure isostatic pressing and hold the pressure for 30 min.
[0053] 4) Place the pressed graphite block in a graphitization furnace for gradient heat treatment. Among them, the atmosphere introduced in the first-stage heat treatment process is nitrogen, the temperature is 1000 °C, and the heat preservation time is 2 h;
[0054] The atmosphere introduced in the second-stage heat treatment process is additive B and a dilution gas. Additive B is gaseous FeCl₃, and the addition amount is 1.5% of the weight of waste graphite. The temperature is 2800 °C, and the heat preservation time is 4 h. The dilution gas is Ar.
[0055] 5) After cooling to 200 °C, the material is discharged. After depolymerization and screening, the graphitized secondary particles are obtained, and the secondary particles are carbonized and coated. Among them, the carbon coating is carried out by liquid-phase coating. Asphalt and tetrahydrofuran solvent accounting for 3-4% of the mass of graphite are added, and they are mixed evenly in a kneading pan. Then the material is placed in a roller hearth kiln for high-temperature carbonization at 1250 °C for 1 h. After carbonization, the material is depolymerized, screened, and demagnetized through conventional methods to obtain the final recycled graphite product.
[0056] Example 2
[0057] Compared with Example 1, the difference is only that the conditions in Step 1 are changed. The experimental groups are as follows:
[0058] Group A: The auxiliary agent A is nano-Fe2O3; ethanol is added to the system in the mixing and resonance stages, and mixing and resonance are carried out based on the liquid-phase method. Among them, the liquid-solid ratio in the treatment stage is 4-5 ml / g, and ethanol is volatilized and removed after mixing to obtain the waste graphite compounded with the auxiliary agent A.
[0059] Group B: The auxiliary agent A is FeCl3; the dosage of the auxiliary agent A is the same as that in Example 1;
[0060] Group C: The ratio of waste graphite powder to nano-Fe3C is 100:0.5; the dosage of the auxiliary agent A is the same as that in Example 1;
[0061] Group D: The auxiliary agent A includes FeCl3 and Fe3C with a weight ratio of 1:1; the dosage of the auxiliary agent A is the same as that in Example 1.
[0062] Other operations and parameters are the same as those in Example 1.
[0063] Example 3
[0064] Compared with Example 1, the difference is only that the conditions in Step 3 are changed, and no pre-pressing treatment is carried out. Other operations and steps are the same as those in Example 1.
[0065] Example 4
[0066] Compared with Example 1, the difference is only that the conditions in Step 4 are changed, and other operations and steps are the same as those in Example 1.
[0067] Group A: The addition amount of FeCl3 is 1.0% of the weight of the waste graphite;
[0068] Group B: The auxiliary agent B is replaced by CoCl2;
[0069] Other operations and parameters are the same as those in Example 1.
[0070] Example 5
[0071] 1) Mix waste graphite powder and additive A (nano Fe₃C) with a mass ratio of 100:1 evenly in advance using a VC mixer, and then place them in a resonance device for secondary mixing. The resonance frequency is 50 Hz and the time is 40 min. After mixing, waste graphite powder loaded with additive A is obtained.
[0072] 2) Evenly mix in advance the waste graphite powder loaded with additive A, crushed petroleum coke, and phenolic resin. The mass ratio of waste graphite powder to petroleum coke is 3:7, and the addition amount of phenolic resin is 5% of the total mass of waste graphite powder and petroleum coke. The D50 of petroleum coke is 8 μm and the volatile content is 8%.
[0073] 3) Place the materials evenly mixed in step 2 in a hot isostatic press. Arrange 4 ultrasonic transducers symmetrically in the isostatic pressure cavity. First, pre-press the materials at 12 MPa at room temperature; then heat up to 280 °C and turn on the ultrasonic wave with a frequency of 30 Hz for ultrasonic-assisted isostatic pressing for 30 min; finally, increase the pressure to 90 MPa for high-pressure isostatic pressing and hold the pressure for 40 min.
[0074] 4) Place the pressed graphite block in a graphitization furnace for gradient heat treatment. Among them, the atmosphere introduced in the first heat treatment process is nitrogen, the temperature is 1200 °C, and the heat preservation time is 1.5 h; the atmosphere introduced in the second heat treatment process is additive B and dilution gas. Additive B is gaseous CoCl₂, and the addition amount is 1.2% of the weight of waste graphite. The temperature is 2600 °C, and the heat preservation time is 6 h. The dilution gas is Ar.
[0075] 5) After cooling to 200 °C, discharge the material, and obtain the final product through steps such as depolymerization, carbon coating, sieving, and demagnetization (for example, the carbon source in the carbonization stage is glucose, and its dosage is 5% of the weight of graphite, the carbonization temperature is 500 °C, and the time is 3 h).
[0076] Example 6
[0077] 1) Mix waste graphite powder and additive A (nano Fe₃C) with a mass ratio of 100:1.5 evenly in advance using a VC mixer, and then place them in a resonance device for secondary mixing. The resonance frequency is 60 Hz and the time is 45 min. After mixing, waste graphite powder loaded with additive A is obtained.
[0078] 2) Evenly mix in advance the waste graphite powder loaded with additive A, crushed petroleum coke, and liquid-phase asphalt. The mass ratio of waste graphite powder to petroleum coke is 4:6, and the addition amount of liquid-phase asphalt is 12% of the total mass of waste graphite powder and petroleum coke.
[0079] 3) Place the uniformly mixed materials from Step 2 into a hot isostatic press. Arrange 4 ultrasonic transducers symmetrically in the isostatic pressure cavity. First, pre-press the materials at room temperature of 15 MPa; then heat up to 200 °C and turn on the ultrasonic wave with a frequency of 35 Hz for ultrasonic-assisted isostatic pressing for 35 min; finally, increase the pressure to 110 MPa for high-pressure isostatic pressing and hold the pressure for 35 min.
[0080] 4) Place the pressed graphite blocks into a graphitization furnace for gradient heat treatment. Among them, the atmosphere introduced during the first heat treatment process is nitrogen, the temperature is 1100 °C, and the heat preservation time is 1.5 h; the atmosphere introduced during the second heat treatment process is additive B and a dilution gas. Additive B is gaseous FeCl3, and the addition amount is 1.2% of the weight of waste graphite. The temperature is 2700 °C, and the heat preservation time is 6 h. The dilution gas is Ar.
[0081] 5) After cooling to 200 °C, discharge the material, and obtain the final product through steps such as depolymerization, carbon coating, sieving, and demagnetization.
[0082] Comparative Example 1
[0083] Compared with Example 1, the difference is only that in Step 1, instead of resonance treatment, VC mixing (for 60 min) is carried out, and then Step 2 and subsequent treatments are carried out. Other operations and parameters are the same as those in Example 1.
[0084] Comparative Example 2
[0085] Compared with Example 1, the difference is only that in Step 2, the ratio of waste graphite powder to petroleum coke is changed to 5:95. Other operations and parameters are the same as those in Example 1.
[0086] Comparative Example 3
[0087] Compared with Example 1, the difference is only that in Step 3, the isostatic pressing treatment is not carried out under ultrasonic assistance. Other operations and parameters are the same as those in Example 1.
[0088] Comparative Example 4
[0089] Compared with Example 1, the difference is only that in Step 4, the atmosphere in the second heat preservation section is Ar, and FeCl3 is not added. Other operations and parameters are the same as those in Example 1.
[0090] Comparative Example 5
[0091] Compared with Example 1, the difference is only that in Step 4, the heat preservation process of the first heat preservation section is missing, and it is directly heated to the second heat treatment temperature for subsequent heat preservation treatment. Other operations and parameters are the same as those in Example 1.
[0092] Battery performance test
[0093] The physical properties of the graphite anode materials obtained in Examples 1 to 6 and Comparative Examples 1 to 5 were respectively tested. The above graphite anode materials were respectively formulated into slurries according to the mass ratio: graphite anode material: carbon black conductive agent SP: binder = 96.5:2:1.5, mechanically stirred at room temperature for 30 min, and the stirring speed was 2000 r / min. The prepared slurry was coated on the current collector, dried in an oven at 100 °C for 30 min, and then dried in a vacuum drying oven at 130 °C for 8 h. The prepared electrode sheets were assembled into lithium-ion coin cells for constant current charge and discharge tests. A lithium sheet was used as the counter electrode, and LiPF6 was dissolved in a mixed solvent of EC / DEC / EMC = 2:3:1 at a concentration of 1 mol / L to form a non-aqueous electrolyte, where EC is ethylene carbonate, EMC is methyl ethyl carbonate, and DEC is diethyl carbonate. The battery was assembled in a glove box for electrochemical performance testing. Charge and discharge regime: First, stand still for 4 h. First discharge: discharge at 0.1C to 0.005V, 0.09C to 0.001V, 0.08C to 0.001V, 0.07C to 0.001V, 0.06C to 0.001V, 0.05C to 0.001V, 0.04C to 0.001V, 0.03C to 0.001V, 0.02C to 0.001V; stand still for 15 min; First charge: charge at 0.1C to 1.5V; stand still for 15 min. Discharge at 0.2C to 0.001V, charge at 0.2C to 1.5V, discharge at 6C to 0.001V, charge at 6C to 1.5V. The test results are shown in Table 1.
[0094] Table 1 Comparison of key performance parameters of examples and comparative examples
[0095]
[0096] From the examples and comparative examples, it can be seen that innovatively, the waste graphite is pre-resonantly mixed with additive A to form primary particles, and then ultrasonic-assisted hot isostatic pressing treatment is carried out with a binder and a special proportion of coke raw materials to form high-strength secondary particles. Further, combined with the subsequent combined control of gradient graphitization containing additive B, in this way, based on the internal and external joint cooperation, the problems faced by the regeneration of waste graphite can be solved, and the physical and chemical structure of the material can be optimized, and then an artificial graphite anode material with good rate performance based on waste graphite can be obtained.
[0097] In addition, from Examples 1 and 2, it can also be known that the combination of FeCl3 and Fe3C can further optimize the physical and chemical characteristics of the material, and is expected to further improve the high rate performance of the prepared material. From Examples 1 and 3, it can be seen that pre-pressing the system in advance and ultrasonic-assisted hot isostatic pressing are expected to further significantly shorten the graphitization preparation process and parameters, and are also expected to improve the high rate performance of the regenerated material.
Claims
1. A preparation method of a waste graphite-based high-rate artificial graphite negative electrode material, characterized in that, Resonance mixing treatment is performed on waste graphite powder and additive A to obtain primary particles; wherein the additive A comprises at least one of boric acid, boron carbide, boron nitride, boron oxide, iron carbide, metal M and its compound; the metal M comprises at least one of iron, cobalt, nickel, chromium, molybdenum, manganese and magnesium; the compound of metal M comprises one or more of oxide, sulfide, halide, metal salt and metal organic complex of metal M; The primary particles, the binder and the coke raw material are subjected to hot isostatic pressing under the assistance of ultrasound to obtain secondary particles; wherein the weight ratio of the waste graphite powder and the coke raw material in the primary particles is 1-4:6-9; The secondary particles are preliminarily subjected to a first stage of heat preservation treatment at a temperature of 800 to 1200° C. in an atmosphere A containing a protective gas, and then subjected to a second stage of heat preservation treatment at a temperature of 2000 to 2800° C. in an atmosphere B containing an additive B, to obtain a graphite material; the additive B is at least one of FeCl3, NiCl, and CoCl2; The graphite material is post-processed to obtain the waste graphite-based rate-type artificial graphite negative electrode material.
2. The preparation method according to claim 1, wherein, The waste graphite powder is graphite-containing waste obtained by disassembling and peeling waste batteries; Preferably, the content of graphite in the waste graphite powder is above 90wt.%; Preferably, the D50 of the waste graphite powder is 8-20 um, and the ash content is less than 10 wt.%.
3. The preparation method according to claim 1, characterized in that, The auxiliary agent A is at least one of nano Fe3C, nano Fe2O3, FeCl3, NiCl, and CoCl2; Preferably, the auxiliary agent A comprises Fe3C and FeCl3; further, the weight ratio of the two is preferably 0.5 to 2:1; Preferably, the weight ratio of waste graphite powder to additive A is 1:0.001-0.05; Preferably, the particle size of the primary particles is 8 to 15 μm; Preferably, the frequency of the resonant mixing is 30 to 100 Hz, and the time is 0.5 to 2 hours.
4. The preparation method according to claim 1, characterized in that, The binder comprises at least one of vinyl tar, byproduct tar, sodium carboxymethyl cellulose, resin, liquid asphalt, water, and polymer starch; Preferably, the binder is 0.5-20% of the total weight of the old graphite powder and the coke raw material, and further preferably 5-15%; Preferably, the coke raw material includes at least one of petroleum coke and needle coke; Preferably, the volatile matter of the coke raw material is greater than 6%, and D506 is 15 um.
5. The preparation method according to claim 1, characterized in that, In the ultrasonic-assisted hot isostatic pressing stage, the ultrasonic power is 5 to 50 Hz; the temperature is 50 to 300°C; and the pressure is 10 to 200 MPa; Preferably, before the ultrasonic assisted hot isostatic pressing treatment, the mixture of the primary particles, the binder and the coke raw material is pre-pressed; Preferably, the pressure of the pre-pressing treatment can be 5 to 20 MPa; Preferably, the pre-pressing time may be 20 to 50 minutes.
6. The preparation method according to claim 1, wherein, The protective gas in atmosphere A includes at least one of nitrogen and inert gas; Preferably, the first insulation period is 0.5 to 12 hours.
7. The preparation method according to claim 1, characterized in that, During the second heat preservation process, the additive B in the atmosphere B includes FeCl3; Preferably, in atmosphere B, a diluting gas is further included, and the dosage of additive B is 0.05-10% of the weight of waste graphite; Preferably, the holding time in the second stage is 2-8 h; Preferably, the post-treatment process includes a step of carbon coating treatment on the graphite material.
8. The waste graphite-based rate-type artificial graphite negative electrode material prepared by the preparation method according to any one of claims 1-7.
9. Use of the waste graphite-based rate-type artificial graphite anode material prepared by the preparation method according to any one of claims 1 to 7, characterized in that, Using it as a negative electrode active material to prepare an alkali metal ion battery.
10. An alkali metal ion battery, characterized in that, It includes the waste graphite-based rate-type artificial graphite negative electrode material prepared by the preparation method according to any one of claims 1-7.
Citation Information
Cited By
Waste coke regenerated graphite, preparation method and application thereof, and lithium ion battery
CN121717360A
Waste coke regenerated graphite, preparation method and application thereof, and lithium ion battery
CN121717360B